A comprehensive study of research and development in concentrating solar cookers (CSCs): Design considerations, recent advancements, and economics. (October 2022) - Gorjian, Alireza; Rahmati, Edris; Gorjian, Shiva; Anand, Abhishek; Jathar, Laxmikant D.
Abstract: Cooking is known to be one of the most energy-intensive sectors, with an estimated energy consumption of about 30–40% of global energy consumption, with a significant share in developing and underdeveloped countries. Traditional cooking, mainly based on biomass and fossil fuels, is one of the main sources of particulate matter (PM) emissions in household buildings, which is an important risk factor for lung cancer. Due to the negative impact on the environment and the waste of energy by traditional cooking systems, innovative and environmentally friendly cooking technologies are becoming more and more popular. Solar energy, as a renewable resource, is best suited for integration into cookers. Several researchers have studied solar cooking technologies to improve their performance and support their use worldwide. Among various solar cooking technologies, concentrating solar cookers (CSCs) have recently attracted much attention, especially in large-scale cooking, due to their special characteristics of generating high temperatures and significantly reducing cooking time. This study has focused on CSCs including parabolic through solar cookers (PTSCs), parabolic dish solar cookers (PDSCs), and Fresnel lens solar cookers (FLSCs), and describes their various aspects, including their operating principles, design considerations, thermal operation, and test procedures, while recent progress in the research and evolvement of these cookers are comprehensively discussed, taking into account their economic aspects. The major drawback of CSCs remains their high initial cost, especially when thermal energy storage (TES) is integrated. However, overcoming the limitations and realizing the great advantages of CSCs to replace them with other cooking methods can make their use more successful and improve their possibility to become commercial worldwide.